The Effectiveness of PBL and TPS Models on Learning Outcomes and Confidence Attitudes - Januarsi, Dian; Florentinus, Totok Sumaryanto; Khafid, Muhammad (Journal of Primary Education)
This study aims to determine and analyze the improvement of learning outcomes and students' self-confidence with PBL and TPS models. This study uses an experimental research design with two group pre-test - post-test designs. The study population was fourth-grade students at Elementary School in East Pekalongan sub-district. Samples were taken by random sampling technique obtained by 114 children from Public Elementary School Klego 01 as many as 61 students, and Public Elementary School Poncol 2 as many as 53 students. Research data were taken from tests and observations. The data were analysed using t-test analysis, with SPSS 23 software. The results showed PBL models are more effective than TPS models on learning theme VIII sub-theme 3 learning 3 with t-test sig values < 0.05. The research concludes that the PBL and TPS models are effective in improving learning outcomes and students' self-confidence. The PBL model is more effective than the TPS model in improving student learning outcomes and self-confidence.